2021
DOI: 10.3390/pharmaceutics13050724
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration Improvement of Co-Cr-Mo Alloy Produced by Additive Manufacturing

Abstract: Cobalt-base alloys (Co-Cr-Mo) are widely employed in dentistry and orthopedic implants due to their biocompatibility, high mechanical strength and wear resistance. The osseointegration of implants can be improved by surface modification techniques. However, complex geometries obtained by additive manufacturing (AM) limits the efficiency of mechanical-based surface modification techniques. Therefore, plasma immersion ion implantation (PIII) is the best alternative, creating nanotopography even in complex struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Statistically, all possible comparisons showed significant differences between groups (p < 0.05). These results suggest that a stimulus is necessary for bone repair in critical man- In the present study, despite the good results observed in the grafted groups (G2, G3, G4) compared to the control group (G1), complete repair did not occur probably because a postoperative period of 6 weeks was standardized in order to determine the speed of bone formation in response to the protocol used [81,82]. Thus, it is important to observe the longterm results in research with grafting of barrier membranes in animals, because it is still unknown whether long-term mineralization occurs in the soft tissue layer formed under the membrane [3].…”
Section: Microscopic Results and Morphometric Analysis Of Newly Forme...mentioning
confidence: 56%
“…Statistically, all possible comparisons showed significant differences between groups (p < 0.05). These results suggest that a stimulus is necessary for bone repair in critical man- In the present study, despite the good results observed in the grafted groups (G2, G3, G4) compared to the control group (G1), complete repair did not occur probably because a postoperative period of 6 weeks was standardized in order to determine the speed of bone formation in response to the protocol used [81,82]. Thus, it is important to observe the longterm results in research with grafting of barrier membranes in animals, because it is still unknown whether long-term mineralization occurs in the soft tissue layer formed under the membrane [3].…”
Section: Microscopic Results and Morphometric Analysis Of Newly Forme...mentioning
confidence: 56%
“…There were no complications that needed to be reported and no diseases or signs recommending the removal of an animal (clinical outcome) were observed 40 . In addition, our research group has experience in the method used, as demonstrated by previously published studies 11,[41][42][43] .…”
mentioning
confidence: 99%
“…As a result, plasma immersion ion implantation (PIII) is the most effective alternative as it creates nanotopography even in complex structures. Iatecola et al [ 7 ] investigated the osseointegration results of the three conditions of additively manufactured Co–Cr–Mo alloy: (i) as-built, (ii) after PIII, and (iii) coated with titanium (Ti) followed by PIII. The metallic samples were designed with a solid half and a porous half to observe the bone ingrowth for different surfaces.…”
Section: Use Of Superficially Modified Porous Metals or Metal Alloys ...mentioning
confidence: 99%